2021
DOI: 10.5530/ijper.55.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Hesperidin against Methotrexate- Induced Nephrotoxicity may be Mediated by Nrf2/HO-1 Pathway

Abstract: Background: Methotrexate (MTX), a successfully used chemotherapeutic in the treatment of various malignancies and autoimmune diseases, might cause severe nephrotoxicity. Here, we aimed at investigating possible nephroprotective effects of hesperidin (HES), a flavanone present in citrus fruits, against MTX-induced toxicity. Methods: Rats were divided into control, HES, MTX, and MTX/HES groups, where HES was administered in a dose of 100 mg/kg/day orally for 8 days and MTX in a single i.p. dose of 20 mg/kg on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…On the opposite side, Nrf2 and HO-1 were significantly up-regulated in the hypothyroid group treated with HSP. Our results confirmed prior studies where HSP showed a cyto-protective effect by up-regulating Nrf2/HO-1 pathway in testicular toxicity [ 96 ] and nephrotoxicity [ 16 , 97 ]. In the same trend, treating hypothyroid rats with ELT significantly increased Nrf2/HO-1 signaling.…”
Section: Discussionsupporting
confidence: 92%
“…On the opposite side, Nrf2 and HO-1 were significantly up-regulated in the hypothyroid group treated with HSP. Our results confirmed prior studies where HSP showed a cyto-protective effect by up-regulating Nrf2/HO-1 pathway in testicular toxicity [ 96 ] and nephrotoxicity [ 16 , 97 ]. In the same trend, treating hypothyroid rats with ELT significantly increased Nrf2/HO-1 signaling.…”
Section: Discussionsupporting
confidence: 92%